Expression Analysis of FANCD2 in Endometrial Carcinoma - Zhang L; Chang J; Wu X (Cancer Management and Research)
Li Zhang,1 Juan Chang,2 Xiuwei Wu2 1Department of Obstetrics and Gynecology, Taihe Hospital, Hubei University of Medicine, Shiyan, Hubei, 442000, People’s Republic of China; 2Department of Hematology, Taihe Hospital, Hubei University of Medicine, Shiyan, Hubei, 442000, People’s Republic of ChinaCorrespondence: Xiuwei Wu, Department of Hematology, Taihe Hospital, Hubei University of Medicine, Renmin Southern 32, Shiyan, Hubei, 442000, People’s Republic of China, Email wuxiuwei2008@126.comBackground: Cisplatin is a major chemotherapy drug in the treatment of Uterine Corpus Endometrial carcinoma (UCEC), and drug resistance often limits its efficacy. Studying the mechanism of cisplatin resistance in endometrial carcinoma is of great clinical importance. This study aims to analyze the expression and value of FANCD2 in UCEC.Methods: The expression of FANCD2, prognosis, and relationship between FANCD2 and immune cell infiltration in UCEC were analyzed by using bioinformatics. The expression levels of FANCD2 in 62 cases of endometrial carcinoma and 28 cases of normal endometrial tissues were detected by RT-PCR, and the relationship between FANCD2 expression and clinicopathological features was analyzed. A FANCD2 knockdown plasmid was constructed and transfected into Ishikawa cells to detect the levels of GSH and MDA in the presence of different concentrations of cisplatin.Results: Bioinformatics analysis showed that FANCD2 was highly expressed in UCEC tissues, and patients with high expression had poor prognosis. Immune infiltration analysis revealed that (B cell, CD8 T cell, macrophage, neutrophil, dendritic cell) infiltration was negatively correlated with FANCD2 expression. Compared with those in Ishikawa-Vector, the levels of GSH significantly decreased and those of MDA significantly increased in Ishikawa-FANCD2KD treated with different concentrations of cisplatin.Conclusion: FANCD2 was highly expressed in UCEC, and the down-regulation of FANCD2 affected the levels of GSH and MDA to increase the cisplatin sensitivity of Ishikawa cells.Keywords: endometrial carcinoma, FANCD2, cisplatin, CD8 T cells